Arabinogalactan-proteins and the research challenges for these enigmatic plant cell surface proteoglycans - Tan, Li; Showalter, Allan M.; Egelund, Jack; Hernandez-Sanchez, Arianna; Doblin, Monika S.; Bacic, Antony (Frontiers in Plant Science, 2012)
N/A